Neuropsychological evaluation of mild head injury. Issue 2 (February 1985) - Gentilini, M; Nichelli, P; Schoenhuber, R; Bortolotti, P; Tonelli, L; Falasca, A; Merli, G A
Abstract : Neuropsychological deficits following mild head injury have been reported recently in the literature. The purpose of this study was to investigate this issue with a strict methodological approach. The neuropsychological performance of 50 mildly head injured patients was compared with that of 50 normal controls chosen with the case-control approach. No conclusive evidence was found that mild head injury causes cognitive impairment one month after the trauma.